1981
DOI: 10.3758/bf03204836
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification thresholds for consonant-vowel syllables

Abstract: Detection and identification thresholds were obtained for 6-and lO-year-old normal children and normal adults using five-formant synthesized consonant-vowel ([ba]-[da]-[ga)l stimuli. Sixyear-old children were found to have poorer detection than adults, just as they do for pure tones. For the identification task, the slopes of the performance-intensity functions were more shallow for 6-year-old children than for lO-year-olds and adults. Consequently, compared with lO-yearolds and adults, 6-year-old listeners re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The findings of higher identification thresholds for 6-year-old children than for adults and a significant age-bysyllable interaction concurred with previous results (Elliott et al, 1981 These types of trends occurred in other work (Elliott et al, 1981a but were less "angular. "…”
Section: Ill Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of higher identification thresholds for 6-year-old children than for adults and a significant age-bysyllable interaction concurred with previous results (Elliott et al, 1981 These types of trends occurred in other work (Elliott et al, 1981a but were less "angular. "…”
Section: Ill Discussionsupporting
confidence: 89%
“…Here, "experimental control" is used in the sense of maintaining a set to respond (Pick and Pick, 1970). This experiment replicated previous work that showed age-related differences in the intensity levels required for syllable identification by children and adults (Elliott et al, 1981a) and also investigated the effects of two test conditions. Both conditions involved presentation of coxasonantvowel (CV) stimuli at different intensity levels.…”
Section: Introductionmentioning
confidence: 61%
“…De velopmental studies generally show that au ditory thresholds decrease rather than in crease through childhood [Eguchi, 1976;Sinnott and Aslin 1983;Elliott, 1979;Elliott et al, 1981;Aslin et al, 1983]. For example, Eilers et al [1981] found that adults, but not prelinguistic infants, were able to discrimi nate a 20-ms VOT difference when VOT was the only acoustic dimension distin guishing /d u / and /tu /.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulus intensity variation has been reported to result in phonemeboundary changes (Dorman & Dougherty, 1981;SyrdalLasky, 1978), but no consistent picture as to the nature and the direction of the changes has yet emerged. On the other hand, it is well established that younger children need higher intensity levels to perform optimally in speech-perception experiments (Elliott, Longinotti, Clifton, & Meyer, 1981). Some link may exist between the facts mentioned above and the age-dependent phoneme-boundary changes.…”
Section: Methodsmentioning
confidence: 99%